Analysis of blood calcium levels in calcium water consumers - Bonni Rubak; Ani Umar; Reymon Reymon; Nanda Reski Jannah (Jurnal Ilmiah Kesehatan Sandi Husada, 2024)
Introduction: Water is a primary and basic human need. One of the chemical parameters that must be met for drinking water needs is mineral content, such as calcium and magnesium. Water hardness is a condition in which there is excessive calcium and magnesium content, which is commonly known as calcareous water. High water hardness that exceeds normal limits can interfere with body health if consumed long-term. Specifically, excess calcium in the body can cause hypercalcemia, hyperparathyroidism, kidney stones, and muscle tissue damage (muscle weakness). Objective: This study aims to determine blood calcium levels in individuals who consume calcareous healthy water. Methods: The type of research used is descriptive-analytical, with blood calcium level analysis carried out using the Ion Selective Electrode (ISE) method through the Electrolyte Analyzer (CBS400). Result: Based on the results of the study, it was obtained that blood calcium levels in 30 community respondents in Ranomeeto District (100%) were above the reference value, indicating high blood calcium levels. Conclusion: blood calcium levels in people who consume lime juice indicate high blood calcium levels. Consuming water with a high lime content can hurt health. Therefore, people need to consider the quality of the drinking water they drink, especially those that have a high lime content, to maintain heart and kidney health in the long term.